ANALISIS PENGARUH STORE ATMOSPHERE TERHADAP IMPULSIVE BUYING DI HYPERMART LOMBOK EPICENTRUM MALL MATARAM - Hidayati, Dwi Nurul (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed to analyst store atmosphere influence towards impulsive buying. The research location was Hypermarket Lombok Epicentrum Mall Mataram. This research is a quantitative associative research. Data were collected from 100 samples. Then data were analyst by using linear regression tool. This research found that general interior, store layout and interior display shown positive influence and significant importance towards consumer impulsive buying. Overall research showed that general interior was more dominant when come to influence consumer impulsive buying. It is recommended that Hypermarket should observe and take into the consideration of the variant store atmosphere with more comprehensive in order to simplify the accuracy of the strategic direction that will create consumer impulsive buying. The management of the hypermarket should be more innovative in changing the exterior of the store by making the outside of the store more attractive and unique.   Keywords    :  Store Atmosphere, Store Exterior, General Interior, Store Layout, Interior Display, and Impulsive Buying.